2017
DOI: 10.3390/app7030226
|View full text |Cite
|
Sign up to set email alerts
|

Optical Beam Deflection Based AFM with Integrated Hardware and Software Platform for an Undergraduate Engineering Laboratory

Abstract: Atomic force microscopy (AFM) has been used extensively in nanoscience research since its invention. Recently, many teaching laboratories in colleges, undergraduate institutions, and even high schools incorporate AFM as an effective teaching tool for nanoscience education. This paper presents an optical beam deflection (OBD) based atomic force microscope, designed specifically for the undergraduate engineering laboratory as a teaching instrument. An electronic module for signal conditioning was built with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…imaging using transmission electron microscopes (TEM) at 4.5m€, scanning electron microscopes (SEM) at 2.4m€ and scanning probe microscopes like atomic force microscopes (AFM) and scanning tunneling microscopes (STM) at 0.7m€. Several research groups have developed their own AFM/STMs and thus a high-quality FOSH AFMs and STMs can be expected in the near term (Babu et al, 2014;Kang, 2015;Li et al, 2016;Loh et al, 2017;Open AFM, 2018). However, the development of both SEM and TEM technologies come with significant hurdles because of the complexity of the technologies and there is thus an opportunity for Finland to benefit from developing FOSH versions of these technologies.…”
Section: Resultsmentioning
confidence: 99%
“…imaging using transmission electron microscopes (TEM) at 4.5m€, scanning electron microscopes (SEM) at 2.4m€ and scanning probe microscopes like atomic force microscopes (AFM) and scanning tunneling microscopes (STM) at 0.7m€. Several research groups have developed their own AFM/STMs and thus a high-quality FOSH AFMs and STMs can be expected in the near term (Babu et al, 2014;Kang, 2015;Li et al, 2016;Loh et al, 2017;Open AFM, 2018). However, the development of both SEM and TEM technologies come with significant hurdles because of the complexity of the technologies and there is thus an opportunity for Finland to benefit from developing FOSH versions of these technologies.…”
Section: Resultsmentioning
confidence: 99%
“…13). The appearance of "elevations" or "depressions" under the tip leads to a change in the force acting on the probe, and hence to a change in the amount of cantilever bending [89].…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…Several projects have focused on building low-cost AFMs that can be used for hands-on nanotechnology educational purposes. Loh et al demonstrated an AFM costing $12,300 for undergraduate laboratories [40] . This AFM can achieve a scan rate of 0.14 lines/s (18 min/frame for 150 × 150 pixels), with lateral and vertical resolutions of up to 20 nm.…”
Section: Hardware In Contextmentioning
confidence: 99%